A polysulfide reduction accelerator – NiS2-modified sulfurized polyacrylonitrile as a high performance cathode material for lithium–sulfur batteries. Issue 42 (18th October 2017) - Liu, Yonggang; Wang, Weikun; Wang, Anbang; Jin, Zhaoqing; Zhao, Hailei; Yang, Yusheng
Abstract : A NiS2 -modified sulfurized polyacrylonitrile composite is prepared by simply co-heating a mixture of sulfur, NiCO3, and polyacrylonitrile. Abstract : A NiS2 -modified sulfurized polyacrylonitrile composite is prepared by simply co-heating a mixture of sulfur, NiCO3, and polyacrylonitrile. The NiS2 –SPAN cathode exhibits superior electrochemical performance, delivering a high reversible capacity of 1533 mA h gsulfur −1 (705 mA h gcomposite −1 ) at 0.2 A g −1 after 100 cycles and good rate capability (1180 mA h gsulfur −1 at 2 A g −1 ).